2002
DOI: 10.1128/aem.68.10.4809-4811.2002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Elemental Sulfur as a Self-Growth-Inhibiting Substance Produced by Legionella pneumophila

Abstract: The addition of HP-20 resin to a medium could enhance the growth of Legionella species. Elemental sulfur was isolated as a self-growth-inhibiting substance produced endogenously by Legionella pneumophila from methanol extracts of the resins used to culture the bacterium. Elemental sulfur shows strong growth-inhibiting activity toward all Legionella species tested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…14 At the same time, sulfur is recognized as an important element for plant growth through balanced fertilization and is sometimes synthesized naturally in its elemental form by some plants and microorganisms as protection. 11,12 Sulfur is indeed more acceptable as a safer organic pesticide for agricultural firms and also a useful nutrient for the plants. 13 Some reports have shown the potential inhibitory effect of sulfur nanoparticles on several microorganisms viz., Pseudomonas areuginosa, Styphylococcus areus, Candida albicans, Aspergillus flavus, Aspergillus niger, Fusarium oxysporum.…”
Section: Introductionmentioning
confidence: 99%
“…14 At the same time, sulfur is recognized as an important element for plant growth through balanced fertilization and is sometimes synthesized naturally in its elemental form by some plants and microorganisms as protection. 11,12 Sulfur is indeed more acceptable as a safer organic pesticide for agricultural firms and also a useful nutrient for the plants. 13 Some reports have shown the potential inhibitory effect of sulfur nanoparticles on several microorganisms viz., Pseudomonas areuginosa, Styphylococcus areus, Candida albicans, Aspergillus flavus, Aspergillus niger, Fusarium oxysporum.…”
Section: Introductionmentioning
confidence: 99%
“…Diaion HP-20 resin is a synthetic absorbent of cross-linked polystyrene, and spherical particles of the resin with diameters of 0.5 mm can be easily recovered by filtration from the culture broth without contamination of the bacterial cells. We recently reported that elemental sulfur was isolated from methanol extracts of Diaion HP-20 resins used to culture the bacteria as a main growth-inhibiting substance produced endogenously by L. pneumophila (Inoue et al, 2002). Since some active fractions other than that containing (60/40) fraction.…”
mentioning
confidence: 99%
“…To date, some biochemical information regarding such growth inhibitors is available; for example, the precise characterization of the high-cell-density culture by Nakano et al (11) revealed that acetic acid serves as a self-growth inhibitor for E. coli. Inoue et al (6) found that the growth of Legionella pneumophila was enhanced by the addition of Diaion resin to the culture, and sulfur was identified as the self-growth inhibitor of this bacterium. It is predicted that the elimination of lactic acid and ammonia is responsible for the growth enhancement of mammalian cells in dialysis culture (9,14).…”
Section: Discussionmentioning
confidence: 99%